Association between delirium and neutrophil percentage-to-albumin ratio in patients with cervical spinal cord injury: A single-center, retrospective study - Kosuke Nitta; Gentaro Kumagai; Kanichiro Wada; Yohshiro Nitobe; Kotaro Aburakawa; On Takeda; Kazushige Koyama; Hirotaka Kinoshita; Tetsuya Kushikata; Kazuyoshi Hirota; Yasuyuki Ishibashi (PLoS ONE, 2026)
Study Design Single-center, case-control study. Objective This study investigated if the neutrophil percentage-to-albumin ratio (NPAR) could predict the onset of delirium in patients with cervical spinal cord injury (CSCI). Background Delirium is a common and serious complication in patients with CSCI, leading to prolonged hospitalization and adverse clinical outcomes. Several risk factors have been identified, but the role of hematologic biomarkers in predicting delirium has remained unclear. While NPAR is a potential marker of systemic inflammation, its association with delirium in CSCI patients has not been established. Methods The analysis included 147 patients with acute CSCI who were admitted to a single tertiary emergency center between 2010 and 2023. Delirium was diagnosed based on the Diagnostic and Statistical Manual of Mental Disorders, Fourth or Fifth Edition criteria. Clinical characteristics, laboratory data, and patient outcomes were compared between those with and without delirium. The association between NPAR and delirium was assessed using receiver operating characteristic (ROC) curve analysis and logistic regression models. Results The incidence of delirium was 10.2% (15/147 patients). ROC analysis identified an NPAR cutoff value of 22 on the day of injury, with an AUC of 0.672. Multivariate logistic regression analysis revealed that an NPAR ≥22 (OR: 7.703, 95% CI: 2.151–27.584, P = .002) was independent risk factors for delirium. Conclusion We found a significant association between a high NPAR (≥22) on the day of injury and the onset of delirium in CSCI patients. NPAR may be an accessible and effective biomarker for early delirium prediction, allowing timely interventions to improve patient outcomes.